KONFLIK SOSIAL DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI KAJIAN SOSIOLOGI SASTRA - Tedi Tahruri; Robert Rizki Yono; Elinda Umisara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Novels as a literary work function as a medium to raise various socialproblems that exist in society. Social conflict in novels can reflect thesocial reality of society as well as the dynamics of relationshipsbetween groups and individuals in everyday life. The purpose of thisstudy is to describe the forms of social conflict and the causes of socialconflict in the novel Pasung Jiwa by Okky Madasari. The method usedin this study is a qualitative descriptive method. The data source for thisstudy is the novel Pasung Jiwa by Okky Madasari in 2013 with 328pages. The form of data in this study is in the form of quotations anddialogues that contain forms of social conflict and the causes of socialconflict according to Soerjono Soekanto. The data analysis techniquefor this study uses the opinions of Milles and Huberman in Sugiyono.The data analysis technique is carried out interactively andcontinuously. Data analysis used is data reduction, data presentation,and drawing conclusions. The results of the study show that the moredominant form of social conflict is the form of personal conflict with 40data compared to the form of conflict between social classes with 6 dataand the form of political conflict with 2 data. The dominant cause ofsocial conflict is caused by differences between individuals, which have21 data points compared to social conflict caused by culturaldifferences, which have 8 data points, differences in interests, whichhave 16 data points, and social change, which have 3 data points.Thus, the analysis of social conflict in the novel is not only to deepenthe understanding of the story, but can also reveal the social realityimplied in the novel, while also emphasizing the function of literature asa reflection or mirror in the life of society.